Natural Death Versus Known Date-Of-Death: A Qualitative Study of Views on Voluntary Assisted Dying in an Online Course About Death. (March 2023) - Rawlings, Deb; Winsall, Megan; Miller-Lewis, Lauren; Tieman, Jennifer
The study aimed to describe views on Voluntary Assisted Dying (VAD), gleaned through qualitative analysis of participant responses to a set activity, run during the 2018 'Dying2Learn' Massive Open Online Course (MOOC). Data from 508 participants, most of whom identified as health professionals, were analysed using thematic content analysis, and themes generated. A large proportion of participants discussed their personal views related to VAD, specifically around choice, control, dignity, palliative care and dying at home, medical intervention, societal factors, the impact on those left behind, laws and regulations, dying 'naturally', advance care directives, and being in pain. In this study, participants had many different views on the act itself, often divisive, but also with common concepts such as respecting the choices and decisions of others.